"Keeping pace according to the child" during procedures in the paediatric intensive care unit: A grounded theory study. (June 2018) - Iwata, Masayuki; Saiki-Craighill, Shigeko; Nishina, Ryouhei; Doorenbos, Ardith Z.
Abstract: Objective: The goal was to explore how nurses interact with children in the paediatric intensive care unit during potentially painful procedures. Research methodology/design: This was a qualitative research study that used grounded theory approach. Data were collected through participant observation and interviews. Nurse–child interactions were observed and recorded during potentially painful procedures performed by nurses. Following observation of a procedure, nurses were interviewed about their intentions, feelings and emotions during the procedure. Setting: The study took place in a seven-bed paediatric intensive care unit in an academic teaching hospital in Japan. Findings: Children's acceptance of a procedure was induced by nurses' pacing, particularly in a pattern of "keeping pace according to the child." Such pacing involved soothing the child, explaining what was being done to the child at each step and acknowledging the child's emotions. All of these child-centred procedures provoked cooperation from the children even during painful procedures. Conclusions: Our study suggests that a collaborative practice approach, in which nurses use a series of calming tactics, might improve children's perceptions of painful procedures.